The study of a Christian 12-Step Program for Christian Smartphone-Addicted Adolescents: A Biblical Perspective - Shim, Jung Yeon (Journal of religion and health, 2021)
The aim of this study was to explore the suitability of a Christian 12-step program based on a biblical perspective for smartphone-addicted adolescents. The study found that “repentance” and “realizing ones’ calling” were the main similarities between the 12-step program’s core principles and biblical themes. Based on a biblical analysis the 12 step program however features some limitations, including an ambiguous definition of the “great power”, a superficial understanding of sin, and a need to consider adolescents’ characteristics. This study suggests the following strategies: (1) diagnosis of adolescents’ image of God and transformation of this image into a biblical image of God, (2) intervention regarding sin through a holistic perspective, (3) adolescents’ recognition of their own calling, and (4) an adult counselor working to trigger social learning in 12 steps. Finally, for application within Christian counselling, the study suggests a cognitive therapeutic approach based on a biblical image of God and a systematic evaluative process of sin in addicted adolescents.